Strategi dalam Meningkatkan Penjualan terhadap Minat Beli Konsumen di Pedagang Eva Fashion - Harahap, Lokot Muda; Tafonao, Dwi Fatmi Adelina; Faradilla, Ageng Jihan; Munawaroh, Munawaroh (Lembaga Yasin AlSys, 2024)
This research analyzes strategies for increasing sales of consumer buying interest at Eva Fashion traders, using a quantitative approach with a sample of 50 respondents selected through a purposive sampling method. Multiple linear regression analysis with a significance level of 5% shows that the three independent variables have a positive and significant influence on consumer purchasing interest, with product design as the most dominant factor (regression coefficient 0.458, p < 0.05), followed by product quality (0.325, p < 0.05) and product variance (0.217, p < 0.05). The research model produces an R2 value of 0.734, indicating that 73.4% of the variation in purchasing interest can be explained by these three variables, with the practical implication that Fashion Parking traders need to prioritize product design aspects while maintaining the quality and diversity of dance to increase business competitiveness.